PEMBANGUNAN PERISIAN PEMBELAJARAN MOBILE CRTV.cn UNTUK KURSUS DIAGNOUS DAN SENGGARAAN AUDIO VIDEO - Subramaniam, Tamil Selvan; Rubani, Siti Nur Kamariah; Hamzah, Norhasyimah; Ariffin, Arihasnida (Online Journal for TVET Practitioners, 2018)
Today's advancement has affected the technological developments of various aspects and fields. The field of education is also no exception in terms of technology development. The impact of this technology development has given rise to a new learning method known as mobile learning or m-learning. M-learning allows teaching and learning to be done at any time and with no location limits. As a result of the survey, there was no mobile learning software developed for the Diagnous and Audio Video courses as a learning support material at the Faculty of Technical and Vocational Education. Therefore, this study is aimed at developing a mobile learning software for the topic of Color TV Receiver as ABBM which can help in learning beyond the classroom. Learning Software Development CRTV.cn has made the ADDIE model a reference and guide in development. Software implementation was made by uploading CRTV.cn Learning Software at Play Store. The software evaluation phase is carried out by developing a five-stage likert testing instrument. Testing is done to test factors related to the usability and usefulness of the software to the user. Data analysis uses SPSS software version 20. The results show that 54.66% of the agreed-scale response responses indicate that CRTV.cn's Learning Software helps students in learning for Diagnous and Audio Video courses. The results from the findings also show that the use of CRTV.cn Learning Software can be a new method or alternative in the learning process.